Ubiquitous Learning Environments and Technologies
X, 258 p. 82 illus., 70 illus. in color.
Keywords: This book focuses on the design and architecture of ubiquitous learning environments, associated technologies, various learning scenarios supported by these environments, and different contexts that arise in environments where the seamless immersion of formal and informal activities and interactions has the potential to contribute to the learning process. With particular focus on adaptivity for individual learners, the book explores the diminishing boundaries of formal and informal learning, and the potential of location-aware context-sensitive approaches that are emerging as successors to the Web 2.0 paradigm.